Assuring development gains and poverty reduction from trade : the labour mobility and skills trade dimension - Puri, Lakshmi (UN New YorkUS, 2008)
Looks at temporary labour mobility and skills trade as it relates to trade and development from the perspective of both sending and receiving countries. Examines the socio-economic costs and benefits. Argues that progress in allowing temporary movement of labour by means of multilateral and regional or bilateral agreements is important to further good global governance, coherence and solidarity necessary for achieving Millennium Development Goals. Makes recommendations which would ensure the sustained positive effects of migration on development.